Enhanced photovoltaic performances of graphene/Si solar cells by insertion of a MoS2 thin film. Issue 34 (10th August 2015) - Tsuboi, Yuka; Wang, Feijiu; Kozawa, Daichi; Funahashi, Kazuma; Mouri, Shinichiro; Miyauchi, Yuhei; Takenobu, Taishi; Matsuda, Kazunari
Abstract : We demonstrated that the high photovoltaic performances of graphene/Si solar cells by inserting a chemical vapor deposition (CVD)-grown, large MoS2 thin-film layer. Abstract : Transition-metal dichalcogenides exhibit great potential as active materials in optoelectronic devices because of their characteristic band structure. Here, we demonstrated that the photovoltaic performances of graphene/Si Schottky junction solar cells were significantly improved by inserting a chemical vapor deposition (CVD)-grown, large MoS2 thin-film layer. This layer functions as an effective electron-blocking/hole-transporting layer. We also demonstrated that the photovoltaic properties are enhanced with the increasing number of graphene layers and the decreasing thickness of the MoS2 layer. A high photovoltaic conversion efficiency of 11.1% was achieved with the optimized trilayer-graphene/MoS2 / n -Si solar cell.